2018
DOI: 10.3389/fneur.2018.00076
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arterial Thrombolysis for Acute Central Retinal Artery Occlusion: A Systematic Review and Meta-Analysis

Abstract: Background and purposeAcute central retinal artery occlusion (CRAO) is a serious ophthalmologic emergency that may result in monocular blindness. To date, studies evaluating intra-arterial thrombolysis (IAT) have not shown a definitive clinical benefit. We have conducted a systematic review with a meta-analysis to effectively evaluate this treatment option.MethodsA systematic literature search was focused on studies containing five or more patients undergoing IAT that included a control group treated with stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…Therefore, most clinicians base their decision to use thrombolytics in acute retinal ischemia on established stroke protocols. Unfortunately, a reliable improvement in visual function has not been demonstrated in patients treated with thrombolytics following acute retinal ischemia (89,90); no significant improvement in visual function following administration of tPA was reported in a number of retrospective reviews and observational studies (9193), however other observational studies, case reports, and retrospective reviews have suggested that visual function improved following administration of tPA (94101). It is possible that the low rate of vision improvement reported in most studies is related to the time between onset of visual symptoms and the administration of thrombolytics (72,96,101105); in most studies, thrombolytics were administered more than 12 hours after vision loss.…”
Section: Treatment Of Acute Retinal Ischemia (Crao or Brao)mentioning
confidence: 99%
“…Therefore, most clinicians base their decision to use thrombolytics in acute retinal ischemia on established stroke protocols. Unfortunately, a reliable improvement in visual function has not been demonstrated in patients treated with thrombolytics following acute retinal ischemia (89,90); no significant improvement in visual function following administration of tPA was reported in a number of retrospective reviews and observational studies (9193), however other observational studies, case reports, and retrospective reviews have suggested that visual function improved following administration of tPA (94101). It is possible that the low rate of vision improvement reported in most studies is related to the time between onset of visual symptoms and the administration of thrombolytics (72,96,101105); in most studies, thrombolytics were administered more than 12 hours after vision loss.…”
Section: Treatment Of Acute Retinal Ischemia (Crao or Brao)mentioning
confidence: 99%
“…Results have been mixed, with reported visual outcomes of no benefit to surpassing 50% of patients, and with adverse events ranging from minor (headache, pain or hematoma at the access site) to major (TIA, intracranial hemorrhage, and neurologic deficit). 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis by Beatty et al11 in 2007 of the available literature found that 34.9% (n = 87) of patients who underwent thrombolysis had obvious improvement in VA and the results of thrombolysis appeared better than the visual recovery with conservative measures or the natural history of the condition. Additionally, a meta-analysis by Page et al63 found a pooled odds ratio of 3.32 to 3.41 of the controlled studies which was reduced to 2.52–2.65 by the addition of the EAGLE study – still considerably in favour of IAT. However, different outcome measures were used to assess the effectiveness of IAT varying from descriptive improvement in VA from initial VA to quantitative analysis using logMAR.…”
Section: Discussionmentioning
confidence: 99%